Comparison of original and alternative incremental sit-to-stand exercise protocol for anaerobic threshold assessment - Keisuke Nakamura; Yuya Nagasawa; Shoji Sawaki; Yoshihiko Yokokawa (Japanese Society of Physical Fitness and Sports Medicine, 2020)
Anaerobic threshold (AT) is an established parameter of aerobic fitness. The incremental sit-to-stand exercise (ISTS), using one of the activities of daily living, is used to assess physical capacity in patients who are unable to safely pedal or walk. However, the effect of an alternative ISTS protocol on AT remains unclear. The aim of this study was to compare the effect of the original ISTS protocol with an alternative shortened ISTS protocol on AT values in healthy young adults, and to assess the difference in AT values obtained during the ISTS protocols and the cycle ergometer test. Twelve healthy young adults (mean [range] age: 26.8 [22-33] years, 6 men and 6 women) performed the shortened version of the ISTS (S-ISTS), the original version of ISTS (O-ISTS), and cycle ergometer (CE) tests in a randomized order. The AT values of participants were measured during each of the three tests. No significant difference in AT values was observed among the three tests. AT obtained by individuals in the S-ISTS was significantly correlated with that obtained during the O-ISTS and CE tests with r values of 0.96 and 0.81, respectively (p < 0.05). Similar to the O-ISTS and CE test, the S-ISTS test may be used as an exercise test for the assessment of AT in a clinical setting.